Bypass discharge, approach velocities and bar spacing: the three key-parameters to efficiently protect silver eels with inclined racks - Tomanova Sylvie; Tissot Laurence; Tétard Stéphane; Richard Sylvain; Mercier Olivier; Mataix Vincent; Frey Aurélien; Lagarrigue Thierry; Tedesco Pablo A.; Courret Dominique (Knowledge and Management of Aquatic Ecosystems, 2023)
Hydropower energy can contribute to achieve the carbon neutrality goals, but also needs to reach environmental sustainability. Hydropower plants (HPP) constitute barriers to fish migrations that are essential for accomplishing their complete biological cycle. Fish downstream passage solutions (FDPS) have to be implemented to maximize their survival, guiding them away from the turbine intakes towards a safe passage alternative. Recent telemetry studies confirmed the efficiency of 26° inclined low bar spacing (20 mm) rack associated to surface bypasses, installed upstream HPPs, to protect downstream migrating Atlantic salmon smolts. Here we tested the efficiency of such FDPS for eel protection using radiotelemetry at four successive HPPs (with intake capacities from 28 to 45 m3.s−1) in the Ariège River (southern France). Between 52 and 74 eels, longer than 550 mm, entered the HPP intakes and 100% of them were protected from turbine passage. All eels crossed the HPP water intake using the surface bypasses, and the great majority in few minutes from their first presentation in front of the rack. These results showed that in such rack configuration, it is not necessary to add a specific bottom bypass, usually recommended for eels. We also showed the importance of optimal hydraulic conditions, mainly tangential (parallel to the rack) velocity and bypass discharge, to efficiently guide the eels towards the surface bypasses, reducing their passage time. Overall, our study provided key elements to water managers for designing an efficient FDPS for eels.